In vivo and in vitro examination of the functional significances of novel lamin gene mutations in heart failure patients. Issue 8 (1st August 2005) - Sylvius, N; Bilinska, Z T; Veinot, J P; Fidzianska, A; Bolongo, P M; Poon, S; McKeown, P; Davies, R A; Chan, K-L; Tang, A S L; Dyack, S; Grzybowski, J; et al.
Abstract : Context: Lamin A/C ( LMNA ) gene variations have been reported in more than one third of genotyped families with dilated cardiomyopathy (DCM). However, the relationship between LMNA mutation and the development of DCM is poorly understood. Methods and results: We found that end stage DCM patients carrying LMNA mutations displayed either dramatic ultrastructural changes of the cardiomyocyte nucleus (D192G) or nonspecific changes (R541S). Overexpression of the D192G lamin C dramatically increased the size of intranuclear speckles and reduced their number. This phenotype was only partially reversed by coexpression of the D192G and wild type lamin C. Moreover, the D192G mutation precludes insertion of lamin C into the nuclear envelope when co-transfected with the D192G lamin A. By contrast, the R541S phenotype was entirely reversed by coexpression of the R541S and wild type lamin C. As lamin speckle size is known to be correlated with regulation of transcription, we assessed the SUMO1 distribution pattern in the presence of mutated lamin C and showed that D192G lamin C expression totally disrupts the SUMO1 pattern. Conclusion: Our in vivo and in vitro results question the relationship of causality between LMNA mutations and the development of heart failure in some DCM patients and therefore, the reliability of genetic counselling. However, LMNA mutations producing speckles result not only in nuclear envelope structural damage, but may also lead to the dysregulation of cellular functions controlled by sumoylation, such as transcription, chromosome organisation, and nuclear trafficking.